Interface Optimization and Thermal Conductivity of Cu/Diamond Composites by Spark Plasma Sintering Process - Junfeng Zhao; Hao Su; Kai Li; Haijuan Mei; Junliang Zhang; Weiping Gong (Nanomaterials)
Cu/Diamond (Cu/Dia) composites are regarded as next-generation thermal dissipation materials and hold tremendous potential for use in future high-power electronic devices. The interface structure between the Cu matrix and the diamond has a significant impact on the thermophysical properties of the composite materials. In this study, Cu/Dia composite materials were fabricated using the Spark Plasma Sintering (SPS) process. The results indicate that the agglomeration of diamond particles decreases with increasing particle size and that a uniform distribution is achieved at 200 μm. With an increase in the sintering temperature, the interface bonding is first optimized and then weakened, with the optimal sintering temperature being 900 °C. The addition of Cr to the Cu matrix leads to the formation of Cr7C3 after sintering, which enhances the relative density and bonding strength at the interface, transitioning it from a physical bond to a metallurgical bond. Optimizing the diamond particle size increased the thermal conductivity from 310 W/m K to 386 W/m K, while further optimizing the interface led to a significant increase to 516 W/m K, representing an overall improvement of approximately 66%.